Cambridge handbook of routine dynamics - Feldman, Martha S., 1953- (Cambridge : Cambridge University Press, 2021)
Over the last two decades, Routine Dynamics has emerged as an international research community that shares a particular approach to organizational phenomena. At the heart of this approach is an interest in examining the emergence, reproduction, replication and change of routines as recognizable patterns of actions. In contrast to other research communities interested in those phenomena, Routine Dynamics studies are informed by a distinctive set of theories (especially practice theory and related process-informed theories). This Handbook offers both an accessible introduction to core concepts and approaches in Routine Dynamics as well as a comprehensive and authoritative overview of research in different areas of Routine Dynamics. The chapters of this Handbook are structured around four core themes: 1) Theoretical resources for research on the dynamics of routines, 2) Methodological issues in studying the dynamics routines, 3) Themes in Routine Dynamics research and 4) Relation of Routine Dynamics to other communities of thought.
What is Routine Dynamics -- Practice theory and Routine Dynamics -- Process theorizing and Routine Dynamics -- Ethnomethodology and Routine Dynamics -- Pragmatism and Routine Dynamics -- Actor-Network Theory and Routine Dynamics -- Materiality and Routine Dynamics -- Ethnography and Routine Dynamics -- Video Methods and Routine Dynamics -- Field Experiments in Routine Dynamics -- Agent-based Modeling in Routine Dynamics -- Sequence analysis in Routine Dynamics -- Narrative networks in Routine Dynamics -- Bakhtin's Chronotope and Routine Dynamics -- Truces and Routine Dynamics -- Context, embeddedness and Routine Dynamics -- Routine Interdependence: Intersections, Clusters, Ecologies and Bundles -- Cognition in Routine Dynamics -- Time, temporality and history in Routine Dynamics -- Transfer & replication in Routine Dynamics -- nnovation work and routine dynamics -- Design and Routine Dynamics -- Algorithms & routine dynamics -- Complexity in Routine Dynamics -- Bodies and Routine Dynamics -- Emotion and Routine Dynamics -- Professional identity and Routine Dynamics -- Occupations, professions and routine dynamics -- Management Practice and Routine Dynamics -- Project-based and temporary organizing and Routine Dynamics -- Self-managed Forms of Organizing and Routine Dynamics -- Unexpected events and routine dynamics -- Carnegie School Experiential Learning and Routine and Routine Dynamics Dynamic Capabilities and Routine Dynamics -- Strategy as Practice and Routine Dynamics -- Path dependence and routine dynamics -- Business Process Management and Routine Dynamics.
Title from publisher's bibliographic system (viewed on 13 Dec 2021).
Keywords: Organizational behavior; Task analysis; Organizational sociology